Development of a novel method for intraoperative radiotherapy during kyphoplasty for spinal metastases (Kypho-IORT) - Schneider, Frank; Greineck, Fabian; Clausen, Sven; Mai, Sabine; Obertacke, Udo; Reis, Tina; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2011)
Purpose - Approximately 30% of patients with cancer receive bone metastases, of which 50% are in the spine. Approximately 20% present with unstable lesions requiring surgical intervention, followed by fractionated radiotherapy over 2-4 weeks to prevent early regrowth. Because of the limited survival time of patients with metastatic cancer, novel treatment concepts shortening the overall treatment time or hospitalization are desirable. In this study, we established a novel approach for intraoperative radiotherapy during kyphoplasty (Kypho-IORT), a method that combines stabilizing surgery and radiotherapy within one visit, after estimating the percentage of eligible patients for this treatment. - Methods and Materials - To estimate the percentage of eligible patients, 53 planning CTs (897 vertebrae) of patients with spinal metastases were evaluated. The number of infiltrated vertebrae were counted and classified in groups eligible or not eligible for Kypho-IORT. The Kypho-IORT was performed in a donated body during a standard balloon kyphoplasty using the INTRABEAM system and specially designed applicators. A single dose of 10 Gy (in 10 mm) was delivered over 4 min to the vertebra. This was verified using two ionization chambers and a Monte Carlo simulation. - Results - The estimation of eligible patients resulted in 34% of the evaluated patients, and thus 34% of patients with instable spinal metastases are suitable for Kypho-IORT. This study shows also that, using the approach presented here, it is possible to perform an IORT during kyphoplasty with an additional 15 min operation time. The measurement in the donated body resulted in a maximum dose of 3.8 Gy in the spinal cord. However, the Monte Carlo depth dose simulation in bone tissue showed 68% less dose to the prescription depth. - Conclusion - We present for the first time a system using an x-ray source that can be used for single-dose IORT during kyphoplasty. The described Kypho-IORT can decrease the overall treatment time for up to 34% of patients who usually receive radiotherapy for spinal metastases.